Preparation and characterization of iron-alginate beads with some types of iron used in supplementation and fortification strategies. (January 2018) - Churio, Osmaly; Pizarro, Fernando; Valenzuela, Carolina
Abstract: Our work aimed to develop and characterize different alginate beads with either non-heme iron or a blend of heme/non-heme iron. We chose non-heme iron salts such as ferrous sulfate (FS), ferrous ammonium sulfate (FAS), ferric citrate (FC), ferrous fumarate (FF), and ferrous bis-glycinate chelate (FCH) at different concentrations as a source of iron for our beads. We also chose spray-dried blood cells (SDBC) as a source of heme iron to be mixed with non-heme iron sources for the development of blend beads. FS, FAS and FC did not form beads by the traditional method of external ionic gelation, unlike FF, FCH and their blends with SDBC, which did form beads for every solution concentration. These beads were characterized by iron content, encapsulation efficiency (EE%), size, color, structure by FTIR, morphology, swelling studies and in vitro iron release studies. Blend beads showed a spherical shape, more homogeneous surface, high iron content (31.3 ± 1.4 to 61.1 ± 4.4 mg Fe/g dried beads) and high EE% (57.6 ± 7.7% to 78.5 ± 2.9%). Major structural interactions were of hydrophilic nature, for all beads. Under simulated gastric incubation conditions, blend beads showed higher stability and released less iron (11–13%) than FF and FCH-alginate beads (19–23%). Under simulated intestinal incubation conditions, all beads released their iron content over a 3 h period. Graphical abstract: Highlights: Ferrous fumarate and ferrous bis-glycinate chelate beads were obtained. Blend beads of non-heme/heme iron beads were obtained. The beads showed high iron content. The beads release most of the iron in intestinal conditions. Blend beads could be used in iron supplementation or fortification strategies.